Tetraploid induction through somatic embryogenesis in Panax vietnamensis Ha et Grushv. by colchicine treatment - Truong, Hoai Phong (Elsevier, 2023)
In the present study, the protocol of polyploid induction via somatic embryogenesis of the Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv.) (2n = 2x = 24) was developed. Ex vitro leaf explants were disinfected with AgNPs at concentrations of 0.05, 0.1, 0.2 and 0.5 g/L for 5, 10, 15, 20 and 30 min and cultured on MS medium supplemented with 1.0 mg/L 2,4-D, 0.5 mg/L NAA and 0.2 mg/L Kin for somatic embryogenesis. Globular embryos induced from the leaf explants were treated with colchicine by immersed method at different concentrations of 0, 0.1, 0.2, 0.3, 0.5 and 0.7% for 24, 36, 48 and 72 h. Then, these embryos were cultured on medium supplemented with 1.0 mg/L 2,4-D, 0.5 mg/L NAA and 0.2 mg/L Kin for secondary embryos induction. The ploidy level was identified by counting chromosomes of the root tip of plantlets derived from these secondary embryos. The results showed that the survival rate and somatic embryo induction the highest (65.56% and 29.89%, respectively) at 0.2 g/L AgNPs for 20 min. For colchicine treatment, the increase in the concentration and exposure time of colchicine decreased the survival rate of explants and the number of secondary embryos but increased the abnormal secondary embryo formation. Identifying the ploidy level showed that the treatments with colchicine concentrations from 0.3% to 0.5% for 48 h lead to tetraploid induction rates from 22.22% to 25.92%. The results also revealed that the tetraploids (2n = 4x = 48) had larger stomatal size, lower stomatal density, denser stomatal chloroplast density, and better growth than did the diploids.